Ukraine: ‘Callous disregard for human life’ of Russian forces’ response to Kakhovka dam destruction compounded by its disastrous effects upstream - Amnesty International (Amnesty International, 2023)
As the consequences of the Kakhovka dam destruction continue to unfold, the occupying Russian forces have been endangering lives in flood-afflicted areas following the destruction of the dam, while upstream water shortages and an upheaval of livelihoods point to an impending ecological and economic disaster, Amnesty International said today.
Ukraine
Keywords: 2023-06 June